Analysis Hybrid Model: An Influencing Marketing 3.0 to Purchasing on Postgraduate Program Institutions in Jakarta - Susilo, Wilhelmus Hary; Suryaty, Lili (International Journal of Economics and Financial Issues, 2015)
A concept developed from the influence of marketing 3.0 of the purchase in post graduate institutions of higher education in Jakarta. Research used the quantitative confirmatory method, of structural equation hybrid modeling. Samples used 105 post graduate students at three institutions. Research finding shows confirmatory factors analysis included; building character, communitization, and purchasing, had Ï‡2 (1.94, 222.6 and 546.5), goodness of fit index (GFI) (0.37, 0.59 and 0.62) and comparative fit index (CFI) (0.83, 0.88 and 0.89). Furthermore, construct reliability (CR= 0.93, 0.95 and 0.95), had reliable construct variables. Marginal fitting hybrid model with, Ï‡2 = 82.92, Pvalue = 0.00012, RMSEA = 0.099, GFI = 0.87, AGFI = 0.80 and CFI = 0.98. The hypothesis; influence communitization marketing 3.0 to the purchasing decision with tvalue = 3.74, successfully confirmed then the influence of building character with purchasing decisions with tvalue = 1.04, in confirmed, furthermore the influence of communitization and building character marketing 3.0 to purchase decisions simultaneously, R2 = 0.81 had a good influence. Finally test between the dimensions’ variable and has the most superior and significant correlation was connection between the consumer and the dimensions of the situation with a value of r (er) = 0.99. Keywords: Purchasing; Marketing 3.0; Superior Dimension JEL Classifications: M000